Bioanalytical challenges and improved detection of circulating levels of IL-13. (February 2016) - Cai, Fang; Hornauer, Hans; Peng, Kun; Schofield, Cheryl A; Scheerens, Heleen; Morimoto, Alyssa M
Background: IL-13 is a key mediator of type 2 inflammation-driven diseases. Circulating IL-13 levels are very low and challenging to detect reliably. We assessed the ability of immunoassays on the Erenna ® and IMPACT platforms to measure serum IL-13 in asthma, idiopathic pulmonary fibrosis (IPF) and atopic dermatitis (AD) patients and in healthy controls (HC).Results: The Erenna IL-13 assay exhibited significant specificity issues and had limited ability to detect IL-13 in serum samples. The IMPACT IL-13 assay had excellent specificity and detected IL-13 in 100% of serum samples tested from asthma, IPF and AD patients and HC. Serum IL-13 levels were significantly elevated in asthma, IPF and AD patients, relative to HC.Conclusion: The IMPACT IL-13 assay had fg/ml sensitivity and excellent specificity, enabling reliable detection of circulating levels of IL-13.